The Dynamics of Dutch Disease in Coffee-Producing Economies - Kubar, Yesım; Ketenci, Seyit Taha; Kurt, Duygu Baysal (My University, 2025)
Coffee producing countries have large production capacities, but the inefficient use of the income earned from the export of this product may have a negative impact on the economic growth rate. The fact that coffee producing countries are the world leaders in terms of coffee production and exports increases the possibility of the Dutch Disease problem in these countries. This has been the main motivation for investigating the existence of Dutch Disease in coffee-producing countries. In this study, the effect of Dutch Disease in the agricultural sector was analyzed by using the variables of coffee production amount, real exchange rate, GDP (gross domestic product), agricultural added value, exports, foreign direct investments and foreign trade deficit of Brazil, Colombia, Indonesia, Honduras, Mexico, Guatemala, Vietnam, Uganda, India, which produce the best coffee among the coffee producing countries and rank first in terms of production amount for the period 1989-2022. The long-term relationship between the variables was examined using the Pedroni panel cointegration test, and a significant cointegration relationship was found in the panel group. Long-term coefficient estimates were obtained using the Fully Modified Ordinary Least Squares (FMOLS) method. The coefficients were found to be statistically significant in both country-level and panel-level analyses. However, no direct evidence was found to support the existence of Dutch Disease. This finding was supported by the Hurlin panel causality test, which revealed that coffee production and exports did not lead to structural deterioration in the agricultural sector, indicating that no Dutch Disease effect was observed.
Keywords: Agricultural sector; Dutch disease; coffee production; cointegration analysis